(untitled) (American Journal of Economics and Business Innovation, 2025)
The impact of social media influencers on consumer engagement and sales conversion on Facebook and Instagram is deliberate in this study. As a quantitative research approach, it quantifies the user engagements and buying patterns, and shows a distinct variance of both the platforms. The study shows that engagement and conversion rates are higher with Instagram compared to Facebook, more so for female users. However, males use Facebook more than other social network sites, Facebook more than any other social network site.